Hubungan Kepatuhan Diet, Konsumsi Magnesium, dan Tingkat Stres dengan Kadar GDP pada Penderita DM Tipe 2 - Rofiqoh, Silfi Layinatul; Damayati, Ratih Putri (Poltekkes Kemenkes Yogyakarta, 2024)
Type 2 diabetes mellitus is a metabolic disease characterized by problems with insulin function, improper insulin, or a combination of both. The risk factors that influence FBG levels are dietary compliance, magnesium consumption, and stress levels. The purpose of this research is to determine the relationship between dietary compliance, magnesium consumption, and stress levels with Fasting Blood Glucose (FBG) levels. This research design uses a cross-sectional approach. The total number of subjects is 97 using purposive sampling techniques. The instruments used are the 24-hour food recall form, FFQ, SQ-FFQ, and Perceived Stress Scale questionnaires. Statistical analysis using the chi-square and multiple logistic regression tests. The research results indicate that there is a relationship between dietary compliance and FBG levels (p=0,000; OR=23,5). There is a relationship between frequency and magnesium intake with FBG levels (p=0,000; OR= 22,5 and p=0,000; OR= 61,5), and there is no relationship between stress levels and FBG levels (p=0,239). Magnesium intake is the most influential risk factor associated with FBG levels (p= 0,001; OR= 123,2). The conclusion of this study is that dietary compliance, frequency and magnesium intake are related to FBG levels, and stress levels not related to FBG levels.